The impact of different diagnostic criteria on the association of sarcopenia with injurious falls in the CLSA. Issue 6 (17th September 2020) - Mayhew, Alexandra J.; Phillips, Stuart M.; Sohel, Nazmul; Thabane, Lehana; McNicholas, Paul D.; de Souza, Russell J.; Parise, Gianni; Raina, Parminder
Abstract: Background: Sarcopenia definitions recommend different combinations of variables (lean mass, strength, and physical function) and different methods of adjusting lean mass. The purpose of this paper was to address the gaps in the literature regarding how differences in the operationalization of sarcopenia impact the association between sarcopenia and injurious falls. Methods: Participants included 9936 individuals from the Canadian Longitudinal Study on Aging aged ≥65 years at baseline (2012–2015), with complete data for sarcopenia‐related variables, injurious falls, and covariates. Sarcopenia was defined using all combinations of muscle variables (lean mass, grip strength, chair rise test, and gait speed) and methods of adjusting lean mass (height 2, weight, body mass index (BMI), and regressing on height and fat mass) recommended by the expert group sarcopenia definitions. Multiple cut off values for the measures were explored. The association between sarcopenia and injurious falls (0, 1, or 2+ falls) measured 18 months after baseline data collection were assessed using proportional odds regression models. Results: In men ( n  = 5162, 72.9 ± 5.6 years), the odds of having a higher level of injurious falls was between 1.43 and 2.14 greater when sarcopenia was defined as (i) lean mass adjusted for weight only; (ii) grip strength (<30 or <26 kg) only; (iii) lean mass adjusted for weight and grip strength (<30 or <26 kg); (iv) lean mass adjusted for BMI and grip strength (<26 kg); and (v) lean mass adjusted using the regression technique and grip strength (<30 or <26 kg). In women ( n  = 4774, 72.8 ± 5.6 years), only the combination of lean mass adjusted using regression with gait speed (<0.8 m/s) was associated with a significantly higher odds (1.46, 95% confidence interval: 1.01–2.10, P  = 0.04) of having a higher level of injurious falls. Conclusions: Sarcopenia definitions based on different combinations of muscle variables and methods of adjusting lean mass are not equally associated with injurious falls. In men, definitions including grip strength but not gait speed or the chair rise test, and adjusting lean mass for weight, BMI, or using the residual technique but not height 2, tended to be associated with injurious falls. In women, sarcopenia was generally not associated with injurious falls regardless of the definition used.